Material properties of the nugget zone in resistance spot-welded DP980 steel joint at various strain rates. (2nd January 2018) - Park, Namsu; Park, Moonsu; Kwon, Junbeom; Huh, Hoon
ABSTRACT: This paper suggests an approach to evaluate the material properties of the nugget zone in resistance spot-welded DP980 steel joints at various strain rates ranging from 0.001 to 100 s −1 . Two kinds of micro-specimens are prepared for the tests: one cut from the centre of the welded nugget zone; and the other cut at 1 mm away from the welded nugget centre. Test results show that the welded nugget zone has little discrepancy in the material properties depending on sampling location and that the flow stress of the nugget zone is relatively high compared with that of the base metal at each strain rate tested. It is confirmed from microscopic observation that the differences are mainly caused by the formation of coarse martensite phase in the welded nugget zone due to the rapid cooling after the resistance spot-welding process.